2019
DOI: 10.1021/acsnano.9b03140
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sequestering Nanocompartments as Multiplexed Electron Microscopy Gene Reporters

Abstract: Multi-colored gene reporters such as fluorescent proteins are indispensable for biomedical research, but equivalent tools for electron microscopy (EM), a gold standard for deciphering mechanistic details of cellular processes 1,2 and uncovering the network architecture of cell-circuits 3,4 , are still sparse and not easily multiplexable. Semi-genetic EM reporters are based on the precipitation of exogenous chemicals 5-9 which may limit spatial precision and tissue penetration and can affect ultrastructure due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…Another promising approach is based on encapsulin-based reporters, which can be expressed in mammalian cells using bioengineering [ 79 , 80 ]. Thus, encapsulins allow iron sequestration via the formation of 10–30-nm particles, which could possibly enable the MRI imaging of the cells.…”
Section: Nanocompartments As Cell and Tissue Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising approach is based on encapsulin-based reporters, which can be expressed in mammalian cells using bioengineering [ 79 , 80 ]. Thus, encapsulins allow iron sequestration via the formation of 10–30-nm particles, which could possibly enable the MRI imaging of the cells.…”
Section: Nanocompartments As Cell and Tissue Markersmentioning
confidence: 99%
“…In one study [ 79 ], Quasibacillus thermotolerans (Qt) and Myxococcus xanthus (Mx) encapsulin expression was achieved by transient co-transfection in HEK293T cells. The cells were transfected with plasmid DNA encoding the encapsulin shell, its cargo protein (ferroxidase enzyme), and iron transporter, which is required for more efficient iron transport.…”
Section: Nanocompartments As Cell and Tissue Markersmentioning
confidence: 99%
“…Previous studies already showed how encapsulin can be employed for liver targeting, vaccine development, imaging or as nanoreactors. 6,20,[32][33][34] Therefore, it is crucial to deepen our knowledge about encapsulin modification and to optimize their production and usability. Hence, this study paves the way for the development of improved encapsulin engineering and production.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies on protein cages can be found for a variety of different applications such as targeted drug delivery, gene reporting and vaccines. [5][6][7] Protein cages are well-defined monodisperse, hollow structures and they are biocompatible thanks to the fact that they are protein based, with a spherical shape, in the range of 1-100nm size. [8][9][10] Among the variety of protein cages, our work focuses on encapsulin cages which were discovered in some bacteria and archaea 11 and may have viral origin shared with the capsid proteins of tailed bacteriophages.…”
Section: Introductionmentioning
confidence: 99%
“…Upon expression in HEK293T cells, this encapsulin protein system self-assemble into nanospheres having icosahedral symmetry that further sequesters and encapsulates ferritin like proteins into it. The mammalian cells harboring this sequestered cargo protein enables its multiplexed gene reporter imaging using the conventional transmission electron microscopy (Sigmund et al, 2019). In magnetotactic bacteria, magA gene encodes for a protein involved in iron sequesteration and transport into the cells.…”
Section: Expression Of Metal Binding Proteinsmentioning
confidence: 99%